PENGARUH SIFAT KEPRIBADIAN CORE SELF EVALUATIONS DAN MOTIVASI PADA KINERJA AUDITOR (STUDI KASUS PADA BPK RI JAKARTA) - Ni Nyoman Sri Rahayu Damayanti; I Made Andika Pradnyana Wistawan (BAJ: Behavioral Accounting Journal, 2018)
An organization stated their own goals and use it as a work guide for the employees. One aspect that is able to support to achieve it, is the performance of employees. BPK is one of institutions that aims to realize a free State implementation from Corruption Collusion and Nepotism (KKN) (Laws of the Indonesian Republic No. 15 of 2006). In order to realize the goals, a good auditor's performance is needed to detect the fairness of government’ financial statements. Core self-evaluation is one of the characteristics that consists of self-evaluation, their abilities, and control of their abilities. CSE are able to predict individual job performance and satisfaction. Job performance also supported by motivation, both from within or extrinsic. The higher the enthusiasm at work, then these things will contribute positively to its performance. The respondents is 31 BPK RI Jakarta auditors. Data was collected through questionnaires. This research used multiple linear regression and showed that CSE and motivation have a positive effect for auditors’ performance.